2013
DOI: 10.1590/0103-6440201302154
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Endodontic Sealer Composition and Time of Fiber Post Cementation on Sealer Adhesiveness to Bovine Root Dentin

Abstract: This study aimed to assess the influence of the type of endodontic sealer (salicylate resin-based sealer vs. two endodontic sealers) and the time of fiber post cementation after root filling on the post adhesion to bovine root dentin. Sixty bovine roots were assigned to six groups (n=10), considering an experimental design with two factors (factorial 3x2): endodontic sealer factor in three levels [epoxy resin-based sealer (AH Plus), eugenol-based sealer (Endofill), and salicylate resin-based sealer plus minera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0
17

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 20 publications
2
23
0
17
Order By: Relevance
“…After the full-text reading of 10 studies, 1 was excluded (11) because of thermocycling samples before the bond strength test. At the final screening, 9 studies (22,24,(28)(29)(30)(31)(32)(33)(34) were included in the meta-analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the full-text reading of 10 studies, 1 was excluded (11) because of thermocycling samples before the bond strength test. At the final screening, 9 studies (22,24,(28)(29)(30)(31)(32)(33)(34) were included in the meta-analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is unclear if the presence of eugenol impairs post retention. Some authors performing different methodologies found a reduction in the retentive capacity of posts cemented after the use of a eugenol-based sealer (11,(17)(18)(19)(20)(21), whereas others did not observe this change (22)(23)(24)(25). Thus, the aim of this study was to systematically review the literature and perform meta-analysis on the influence of eugenol on the bond strength of posts luted to root canals evaluated by the push-out test.…”
mentioning
confidence: 95%
“…They also found higher bond strength values for epoxy resin-based cements, like AH Plus, compared with zinc oxide-eugenol sealers, like Endo Fill. Several other studies also found that the push-out bond strength of AH Plus was superior to that of other root canal sealers [27][28][29] .…”
mentioning
confidence: 96%
“…This sealer is composed of salicylate resin, resin diluent, natural resin, bismuth oxide, silica nanoparticles, and MTA. Its physical properties (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) and biocompatibility (24,25) are already known. Nonetheless, to date, no studies have been conducted to analyze histologically the effect of MTA Fillapex in direct contact with bone tissue.…”
mentioning
confidence: 99%